Comparative efficacy and acceptability of treatments for depressive symptoms in cognitive impairment: A systematic review and Bayesian network meta-analysis - Jin, Boru; Xv, Yunting; Zhang, Bixuan; Qiao, Lei; Liu, Huayan (Frontiers in Aging Neuroscience, 2022)
Background Depressive symptoms play an essential role in cognition decline, while the benefit and acceptability of treatments for depressive symptoms in cognitive impairment are still unknown. Objective To comprehensively evaluate the comparative efficacy and acceptability of treatments for depressive symptoms in cognitive impairment based on the quantitative Bayesian network meta-analysis method (NMA). Method We searched MEDLINE, Embase, the Cochrane Library, CINAHL, and PsycINFO from inception until August 2022 to identify randomized clinical trials (RCTs) evaluating treatments for depressive symptoms in cognitive impairment. Efficacy was evaluated by the Cornell Scale for Depression in Dementia (CSDD), the Hamilton Depression Rating Scale (HDRS), and the Geriatric Depression Scale (GDS) for depression; the Neuropsychiatric Inventory (NPI) and the Cohen–Mansfeld Agitation Inventory (CMAI) for behavior; and the Mini-Mental State Examination (MMSE) for cognition. Safety was evaluated by total adverse events (AEs), serious AEs, diarrhea, headache, and nausea. Results In this study, 13,043 participants from 107 RCTs were included, involving 28 treatments and the discontinuation of antidepressants. On CSDD, aerobic exercise (MD −4.51, 95%CrI −8.60 to −0.37), aripiprazole (MD −1.85, 95%CrI −3.66 to −0.02), behavioral training (MD −1.14, 95%CrI −2.04 to −0.34), electrical current stimulation (MD −3.30, 95%CrI −5.94 to −0.73), massage (MD −12.67, 95%CrI −14.71 to −10.59), music therapy (MD −2.63, 95%CrI −4.72 to −0.58), and reminiscence therapy (MD −2.34, 95%CrI −3.51 to −1.25) significantly outperformed the placebo. On MMSE, cognitive stimulation therapy (MD 1.42, 95%CrI 0.49 to 2.39), electrical current stimulation (MD 4.08, 95%CrI 1.07 to 7.11), and reminiscence therapy (MD 1.31, 95%CrI 0.04 to 2.91) significantly outperformed the placebo. Additionally, no treatments showed a significantly higher risk than the placebo. Conclusion Our NMAs indicated that non-pharmacological interventions were more efficacious and safe than pharmacological treatments for reducing depressive symptoms as well as improving cognitive impairment. Electrical current stimulation, aerobic exercise, and reminiscence therapy could be first recommended considering their beneficial performance on both depression and cognition. Hence, non-pharmacological treatments deserve more attention and extensive application and should at least be considered as an alternative or assistance in clinical settings. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021239621, identifier: CRD42021239621.